Cyclodextrin Formation Initiated by Enzyme Debranching Reaction On Amylopectin Branch Chain Of Tapioka - Laga, Amran (Jurnal Natur Indonesia, 2009)
Degradation of starch by the glucosyltransferase enzyme (CGTase) to produce the primary product of chainsplitting undergoes an intramolecular reaction without the participation of water molecule. From this process, α-1,4-Linked cyclic product, known as cyclodextrins, are formed. The aim of the research was to cut amylopectinbranch in order to produce one straight chain, to optimize cyclic reaction formation cyclodextrin by CGTase. Theresearch was devided into 3 stages; (1) debranching enzyme concentration estimation (5,10,15,20, and 25 unit/gram) and the length of otimum reaction to produce straight chain for 5 hours which sample was taken each hour,(2) reaction length time estimation to form cyclodextrin in order to use debranching products (straight chain) assubstrates, the reaction length for 360 minutes and sample taken each for 30 minutes, and (3) the best substrateconcentration for straight chain (20-40% w/v) to produce cyclodextrin. The result showed that enzyme concentrationtreatment and optimal length reaction will produce straight chain with enzyme concentration of 14 units/gram for3 hours and straight chain product of 20 units/gram for 1 hour with straight chain product of 83.5%. The optimumlength of reaction for cyclodextrin formation from amylose produced from the de-branching process was 240minutes. The amount of cyclodextrin produced was 143.45 g/L with conversion value of 47.81% at 30% (w/v)substrate concentration. Highest yield of cyclodextrin (154,28 g/L) and conversion value of 44.08% was obtained at35% (w/v) substrate concentration